Your social work practice placement : from start to finish - Mathews, Ian; Simpson, Diane; Crawford, Karin (Los Angeles SAGE, 2014)
Embarking on a first practice placement can be an anxious experience for social work students. This textbook takes them step-by-step through the process, holding their hand through preparation for practice modules and during the course of the placement itself. Focusing on practicalities, knowledge, values and skills, the authors guide students through the challenges they may face. Chapters include numerous real-life case examples which reflect a range of varying placement contexts including different settings, service-user groups, locations and areas of practice. The book will help students become confident on placement and lead to rich placement experiences which will benefit them throughout the rest of their degree and upon entry to the profession. This book is essential reading for all social care students.
About the Authors -- Introduction -- Preparation for the Placement -- The Beginning of the Placement -- The Middle of the Placement -- The End of the Placement -- Conclusion -- Glossary of Terms and Abbreviations -- References -- Index
Keywords: Social workers; Social service